The Implementation of the Consciousness-Raising (C-R) Method in Improving EFL Students’ Writing Skills - Suhaimi, Suhaimi; Musdizal, Musdizal (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2022)
The purpose of this study was to determine the extent to which the Consciousness-Raising (C-R) method improves students' writing skills and to identify the factors that influence the improvement process. The study was conducted with third-semester students in the English Department, consisting of 16 students. The research design was Classroom Action Research (CAR) and was carried out in three cycles over a period of 12 weeks, with four meetings including one test in each cycle. The cycles comprised of planning, action, observation, and reflection. Qualitative data was obtained through observation, field notes, and interviews, while quantitative data was obtained from students' writing tests. The results of this study showed improvement in the students' writing skills, as demonstrated by the teaching and learning activities throughout each cycle and the increasing scores of the students' writing tests, which went from 65.45 in cycle 1 to 77.63 in cycle 2 and 88.22 in cycle 3. The decrease in errors in each test cycle also supported this improvement. The observation and field notes indicated that the C-R method increased students' attention and awareness, resulting in more focus and engagement in the learning process. The factors that influenced the improvement of students' writing skills were motivation, the role of the instructor, classroom environment, materials, and media. The C-R method was found to be effective in improving students' writing skills and resolving writing problems. The researcher therefore recommends the use of this method, taking into consideration the supporting factors.